Analysis of the Characteristics of Pore Pressure Coefficient for Two Different Hydrate-Bearing Sediments under Triaxial Shear - Ruchun Wei; Chao Jia; Lele Liu; Nengyou Wu (Journal of Marine Science and Engineering, 2022)
It is important to determine the volumetric change properties of hydrate reservoirs in the process of exploitation. The Skempton pore pressure coefficient <semantics>A</semantics> can characterize the process of volume change of hydrate-bearing sediments under undrained conditions during shearing. However, the interrelationship between <semantics>A</semantics> value responses and deformation behaviors remain elusive. In this study, effects of hydrate saturation and effective confining pressure on the characteristics of pore pressure coefficient <semantics>A</semantics> are explored systematically based on published triaxial undrained compression test data of hydrate-bearing sand and clay-silt sediments. Results show that there is a higher value of the coefficient <semantics>A</semantics> with increasing hydrate saturation at small strain stage during shearing. This effect becomes more obvious when the effective confining pressure increases for hydrate-bearing sand sediments rather than hydrate-bearing clayey-silt sediments. An increasing hydrate saturation leads to a reduction in A values at failure. Although A values at failure of sand sediments increase with increasing effective confining pressure, there are no same monotonic effects on clayey-silt specimens. A values of hydrate-bearing sand sediments firstly go beyond 1/3 and then become lower than 1/3 at failure even lower than 0, while that of hydrate-bearing clayey-silt sediments is always larger than 1/3 when the effective confining pressure is high (e.g., >1 MPa). However, when the effective confining pressure is small (e.g., 100 kPa), that behaves similar to hydrate-bearing sand sediments but always bigger than 0. How the A value changes with hydrate saturation and effective confining pressure is inherently controlled by the alternation of effective mean stress.